2019
DOI: 10.1039/c9ra04241e
|View full text |Cite|
|
Sign up to set email alerts
|

Solvent-controlled synthesis of multicolor photoluminescent carbon dots for bioimaging

Abstract: The synthesis and bioimaging of multicolor carbon dots from citric acid and urea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…22−25 For example, Yan et al have detailed the citric acid-based red, green, and blue emissive CDs in formic acid, ethanol, and HCl, respectively. 21 Chao et al have shown the multicolor emission by dispersing the o-phenylenediamine-based CDs in ethylene glycol, tetrahydrofuran, methanol, acetone, and N,N-dimethylformamide. 25 Recently, some researchers have provided the mechanism for solvatochromism.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…22−25 For example, Yan et al have detailed the citric acid-based red, green, and blue emissive CDs in formic acid, ethanol, and HCl, respectively. 21 Chao et al have shown the multicolor emission by dispersing the o-phenylenediamine-based CDs in ethylene glycol, tetrahydrofuran, methanol, acetone, and N,N-dimethylformamide. 25 Recently, some researchers have provided the mechanism for solvatochromism.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To date, few researchers have developed multicolor wavelength emissive CDs using different solvents. , In general, there are two ways that have conveyed to tune the solvent-dependent fluorescence property of carbon dots. These are either carbon dots that are directly synthesized using different solvents from the same precursor or may be synthesized CDs dispersed in different solvents to observe the tunable property. For example, Yan et al have detailed the citric acid-based red, green, and blue emissive CDs in formic acid, ethanol, and HCl, respectively . Chao et al have shown the multicolor emission by dispersing the o -phenylenediamine-based CDs in ethylene glycol, tetrahydrofuran, methanol, acetone, and N , N -dimethylformamide .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the abundant polar function groups, these simples have good solubility in solvents of polarity, such as water and ethanol (EtOH). [41,42] The peaks at 1530 and 1629 cm −1 can be observed for each sample. These peaks are a result of the stretching vibration in the CC group, which can be considered as the formation of aromatic ring skeleton during synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…9 Currently, increasing research interests of GQDs are focused on multichannel detection by taking advantages of their multicolor emissions, especially in a long wavelength range. 10 For example, Qin et al synthesized polychromatic GQDs from blue to red bands by changing the content of the precursor and the reaction temperature for the application of ion sensing and solid lighting. 11 Zheng et al prepared composite red, green, and blue GQDs by changing the reaction solvent and applying them in LED fields.…”
Section: Introductionmentioning
confidence: 99%
“…Ascribed to their outstanding photoluminescence properties, high stabilities, exceptional biocompatibilities, and inexpensive precursors, , in recent years, great efforts have been made to further develop GQD materials for latent applications such as fluorescence sensing, light-emitting diodes (LEDs), photocatalysis, bioimaging, and drug delivery . Currently, increasing research interests of GQDs are focused on multichannel detection by taking advantages of their multicolor emissions, especially in a long wavelength range . For example, Qin et al synthesized polychromatic GQDs from blue to red bands by changing the content of the precursor and the reaction temperature for the application of ion sensing and solid lighting .…”
Section: Introductionmentioning
confidence: 99%